2014
DOI: 10.1002/j.2161-0045.2014.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Underachievement and Recovery: Student Perspectives on Effective Career Interventions

Abstract: Academic achievement has a significant influence on various career development and decision‐making factors. Therefore, it is important for career counselors to understand how past academic underachievement affects students’ current lives and to develop interventions that might ameliorate negative effects. This study examined the experiences of 9 ethnically diverse college students who had experienced and overcome academic failure. Data were collected by individual interviews and analyzed based on the consensua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The intervention does not grant academic credits (Humphrey, 2005). Hwang et al (2014) came to the same conclusion analyzing the experience of some college students who had experienced academic effectiveness. During the 'education recovery program' four main topics appeared to be vital: attitude, study strategies, external support, and coping with difficulties.…”
mentioning
confidence: 77%
“…The intervention does not grant academic credits (Humphrey, 2005). Hwang et al (2014) came to the same conclusion analyzing the experience of some college students who had experienced academic effectiveness. During the 'education recovery program' four main topics appeared to be vital: attitude, study strategies, external support, and coping with difficulties.…”
mentioning
confidence: 77%
“…On the other hand, all of these results also demonstrate that underachievement is clearly not an irreversible "condition", as many students get back on track later on (see also Uno, Mortimer, Kim & Vuolo, 2010). Support from family and peers, as well as persistence in setting ambitious goals despite the difficulties, appear to be crucial factors for this to happen (Peterson, 2000;Hwang et al, 2014;McCall, 1994), making it all the more important to recognize underachievement as such and not mistake it for an unalterable lack of ability. This is not a trivial task: Rost and Hanses (1997) found that teachers in their study could not identify underachieving students in their classes very well; in a more recent study, teachers had only a moderately accurate impression of their students' attitudes towards school-in particular, they often underestimated their students' goal valuation (Siegle et al, 2020).…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…A number of studies have suggested that, besides the intelligence factor, learning strategies play an important role in distinguishing the learning outcomes of different students. Although students with poor learning effectiveness tend to adopt fewer learning strategies, improving their learning strategies could promote better learning outcomes [ 20 , 21 , 22 ]. Tang et al [ 23 ] show that the combined model of online teaching with the flipped learning improved students’ learning, attention, and evaluation of courses.…”
Section: Literature Reviewmentioning
confidence: 99%